Risk Transmission of Foreign Subsidiary in ASEAN Emerging Countries - Etikah Karyani; Agusman Agusman (ETIKONOMI, 2024)
Research Originality: To the best of our knowledge, this study is the first to investigate the impact of home country parent bank risks on destination country subsidiaries in an ASEAN setting. Moreover, this study adds to the previous literature by using the post-global financial crisis period in ASEAN countries, various  types of risks, and dynamic panel data.Research Objectives: This study aims to examine the association between parent and foreign subsidiary banks. The study also examines how bank regulation, national governance, and financial deepening in host countries affect the association.Research Methods: This study uses dynamic panel data of 43 foreign banks operating in ASEAN emerging countries during the period 2010-2018.Empirical Results: The findings indicate a significantly positive association between parent and subsidiary bank risk, particularly for credit and liquidity risks. National governance and bank regulation mitigate the risk transmission. In contrast, financial deepening amplifies the transmission of risks between parent and subsidiary banks.Implications: This finding has important implications, in terms of policy interventions and regulatory mechanisms that national governments can deploy to lower risk exposure of subsidiary banks, while at the same time encouraging foreign investments into the financial services sectors in ASEAN countries.JEL Classification: F30, G21, G32How to Cite:Karyani, E., & Agusman. (2024). Risk Transmission of Foreign Subsidiary: Evidence from ASEAN Emerging Countries. Etikonomi, 23(1), 129 – 146. https://doi.org/10.15408/etk.v23i1.32703.